A INTERACÃO DE ESTUDANTES DE ENFERMAGEM COM AGRICULTORES NO USO DE AGROTÓXICOS - Poli, Ane G.; Strieder, Alice T.; Franco, Maiara T.; Ubessi, Liamara D.; Stumm, Eniva M. F.; Sandri, Andréia; Nogueira, Gabriela d. M.; Rohing, Elise d. O.; Tishen, Andréia; Kirschner, Rosane M.; Loro, Marli M. (Salão do Conhecimento, 2013)
Resumo